The Effect of Teamwork and Work Dicipline on Employee Performance with Job Satisfaction as an Intervening Variable - Muhammad Faqih Al-Aziz; Eloh Bahiroh; Ana Susi Mulyani (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This research aims to determine the effect of teamwork and work discipline on employee performance with job satisfaction as an intervening variable at Regional Drinking Water Company Tirta Madani, Serang City. This research is a quantitative type of research using a saturated sample method with 50 predetermined respondents. This research uses descriptive statistical t-tests, outer models for measurement, and inner models for structural analysis, all within the SmartPLS 4.0 analysis tool. The results of this research show that: teamwork has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Teamwork has a positive and significant effect on job satisfaction. Work discipline has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction can mediate the relationship between teamwork and employee performance. Job satisfaction can mediate the relationship between work discipline and employee performance.